The Role of Imprisonment and Censorship in the International Success of Pramoedya Ananta Toer’s Buru Quartet Novels - Yani Susanti (Lingua Cultura, 2014)
Imprisonment and censorship that is meant to silence Pramoedya Ananta Toer and his books did not succeed. On the contrary, they only help popularize Pramoedya Ananta Toer’s Buru Quartet novels in the international market. Through some library researches, this article analyzed the purpose of imprisonment, the impacts it has on Pramoedya Ananta Toer’s career in the literary world and related them to Pierre Bourdieu’s concept of capital. It is concluded that this triumph over imprisonment and censorship owes its success to Pramoedya Ananta Toer’s strong connections with the people that matter in his lifetime.